Academics’ Awareness towards Mobile Learning in Oman - Al-Emran, Mostafa; Shaalan, Khaled (ResearchGate, 2017)
Mobile Learning (M-Learning) witnessed a booming evolution contributed to the evolvement of learning within the higher educational settings. M-Learning enhances the collaboration between the educators and their students on anytime anywhere settings. Attitudes towards the utilization of M-Learning help the decision makers in building the required infrastructure. Our literature review indicated that there are very few studies that address the issue of educators’ awareness towards M-Learning which is a very significant factor for the success of smart education. In this study, a questionnaire survey has been administrated at Al Buraimi University College, Oman in order to examine the educators’ awareness and attitudes towards the utilization of M-Learning. Findings revealed that female instructors were more positive than males towards the utilization of M-Learning. Moreover, results revealed that academics who indicated that mobile technology is an effective tool in education were highly optimistic towards the utilization of M-Learning than those who were not. Nevertheless, results were not pointed any significant differences with regard to the academics’ perceptions towards the utilization of M-Learning in relation to age and academic qualifications factors, showing that M-learning can be embraced by all academics irrespective of the age and qualifications factors.